2006
DOI: 10.4039/n05-080
|View full text |Cite
|
Sign up to set email alerts
|

The Mordellidae (Coleoptera) of the Maritime provinces of Canada

Abstract: The Mordellidae of the Maritime provinces of Canada is surveyed. Thirty species have now been recorded from the region. Of these, 17 are newly recorded for Nova Scotia, 11 are newly recorded for Prince Edward Island, and 7 are newly recorded for New Brunswick, for a total of 35 new provincial records. Three species, Mordellistena indistincta Smith, Mordellistena rubrifascia Liljeblad, and Mordellistena rubrilabris Helmuth, are newly recorded for Canada, while a further 11 species, Mordella melaena Germar, Mord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 5 publications
(7 reference statements)
0
11
0
Order By: Relevance
“…This may represent an island-associated diminution, a paucity of collecting, or a combination of both. Majka & McCorquodale (2006) found that Cape Breton Island had 41% of the Maritime Provinces fauna of native Coccinellidae, and Majka and Jackman (2006) found the same proportion (41%) of native Mordellidae. In examining the saproxylic Tetratomidae, Melandryidae, Synchroidae, and Scraptiidae, Majka & Pollock (2006) found 32% of the native Maritime species on Cape Breton, while Majka (2006) examining another grouping of saproxylic families, the Mycteridae, Boridae, Pythidae, Pyrochroidae, and Salpingidae, found 53% of the Maritime Provinces species on Cape Breton.…”
Section: Contemporary Composition and Zoogeographymentioning
confidence: 92%
“…This may represent an island-associated diminution, a paucity of collecting, or a combination of both. Majka & McCorquodale (2006) found that Cape Breton Island had 41% of the Maritime Provinces fauna of native Coccinellidae, and Majka and Jackman (2006) found the same proportion (41%) of native Mordellidae. In examining the saproxylic Tetratomidae, Melandryidae, Synchroidae, and Scraptiidae, Majka & Pollock (2006) found 32% of the native Maritime species on Cape Breton, while Majka (2006) examining another grouping of saproxylic families, the Mycteridae, Boridae, Pythidae, Pyrochroidae, and Salpingidae, found 53% of the Maritime Provinces species on Cape Breton.…”
Section: Contemporary Composition and Zoogeographymentioning
confidence: 92%
“…Th is may represent an island-associated diminution, the paucity of collecting, an area effect, or a combination of all these factors. In comparison, Majka and McCorquodale (2006) found that Prince Edward Island had 39% of the native Maritime Provinces fauna of Coccinellidae, Majka and Jackman (2006) found 40% of Maritime species of Mordellidae, Majka et al (2007) found 32% of the native Maritime Cerambycidae, and Majka et al (2008) found 49% of the native Maritime Carabidae that occur on Prince Edward Island.…”
Section: Discussionmentioning
confidence: 99%
“…In practice this means stands where trees average 150 years (sugar maple, yellow birch, beech), 200 years (red spruce and white pine) or 300 years (eastern hemlock) depending on species composition. Majka (2006Majka ( , 2007, Majka and Jackman (2006), Majka and Pollock (2006), (Majka et al , 2007a.…”
Section: Discussionmentioning
confidence: 99%